Postprandial thermogenesis in Bothrops moojeni (Serpentes: Viperidae) - Stuginski, D. R.; Fernandes, W.; Tattersall, G. J.; Abe, Augusto Shinya [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Snakes that can ingest prey that are proportionally large have high metabolic rates during digestion. This great increase in metabolic rate (specific dynamic action - SDA) may create a significant augment in the animal's body temperature. The present study investigated postprandial thermogenesis in Bothrops moojeni. Briefly, two groups of snakes were fed meals equivalent to 17 +/- 3% and 32 +/- 5% of their body weight and were observed for 72 hours, in which thermal images of each snake were taken with an infrared camera in a thermostable environment with a constant air temperature of 30 degrees C. The results showed a significant increase in snake surface temperature, with a thermal peak between 33 and 36 hours after feeding. The meal size had a great impact on the intensity and duration of the thermogenic response. Such increase in temperature appears to be connected with the huge increase in metabolic rates during digestion of relatively large prey by snakes that feed infrequently. The ecologic implication of the thermogenic response is still not well understood; however, it is possible that its presence could affect behaviors associated with the snake digestion, such as postprandial thermophily.
Keywords: Bothrops; thermogenesis; feeding behavior; digestion